Penguatan Perlindungan Hak Pekerja Rumah Tangga: Urgensi Ratifikasi Konvensi ILO 189 dan Dampaknya Terhadap RUU PPRT Indonesia - Naia Afra Rayandi; Nisrina Putri Fauzi (CV Rewang Rencang, 2025)
The issue of Domestic Workers (PRT) is not uncommon in Indonesian society. Domestic workers are people who provide services to employers to complete household chores. Domestic workers in Indonesia are still one of the most marginalized groups of workers due to the absence of a legal framework capable of regulating and protecting their rights. The International Labor Organization (ILO) paid special attention to the issue of protecting domestic workers by issuing ILO Convention 189 on Decent Work for Domestic Workers. This article analyzes the urgency of ratifying ILO Convention 189 to encourage the protection and promotion of the rights of domestic workers, especially by evaluating the provisions of the convention and their potential for adoption in the PPRT Bill.